2005
DOI: 10.1111/j.1440-1754.2005.00754.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of early transfer of premature infants from incubators to cots: A pilot study

Abstract: The results of this pilot study indicate the potential to transfer very low birthweight infants to an open unheated cot at a bodyweight of 1500 g. This study provides information for the design of future randomized controlled trials that are required to confirm the findings of this study before routine adoption of this intervention into clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
22
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 11 publications
5
22
2
Order By: Relevance
“…A heterogeneous patient population in this small study showed increased growth at warmer incubator temperatures compared with a cooler environment. Our data support the recent study by West et al 10 and Berger et al's 11 preliminary data, which showed no decrease in weight gain following incubator wean to open crib. The ParadigmHealth database, as one of the largest data sets published on this topic, further shows the consequences in delaying appropriate incubator weaning, such as delayed oral feedings and prolonged length of hospitalization.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…A heterogeneous patient population in this small study showed increased growth at warmer incubator temperatures compared with a cooler environment. Our data support the recent study by West et al 10 and Berger et al's 11 preliminary data, which showed no decrease in weight gain following incubator wean to open crib. The ParadigmHealth database, as one of the largest data sets published on this topic, further shows the consequences in delaying appropriate incubator weaning, such as delayed oral feedings and prolonged length of hospitalization.…”
Section: Discussionsupporting
confidence: 83%
“…An appropriate starting point would be to develop standardized incubator weaning protocols based on physiological principles and evidence based medicine. Medoff-Cooper et al, 9 West et al, 10 Berger et al, 11 Meier,15 as well as the Association for Women's Health, Obstetric, and Neonatal Nursing (AWHONN) Research Utilization Project 16 support our data that successful incubator weaning can begin at infant weights approximating 1500 g. In addition, though this study evaluated infants less than 31-weeks GA, consideration to begin incubator weaning at 1500 g in a more mature GA patient population seems reasonable given their physiological stability in comparison with the study group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified one randomised9 and two quasi-randomised6 7 controlled trials and five observational studies3 8 1214 assessing transferring preterm infants to standard open cots. Sutter and colleagues7 showed that preterm infants could be safely transferred to open cots at 1700 g but only for infants with birth weights >1000 g. However, they expressed caution in interpreting the results, due to the small number of infants with birth weights <1000 g (n=12).…”
Section: Discussionmentioning
confidence: 99%
“…There was evidence from two quasi-randomised studies suggesting that transfer to an open cot may safely occur at weights ≥16006 or ≥1700 g 7. More recent studies suggest potential transfer at 1500 g8 and at 1600 g 9…”
Section: Introductionmentioning
confidence: 99%